KONSEP IPTEK DAN KETERPADUANNYA DALAM ALQURAN - Syaifullah MS (State Institute of Islamic Studies (IAIN) Palu, 2006)
Science and technology emerge not without any reason. They emerge as the result of deep thought of human beings due to their life needs. Besides, science and technology are highly influenced by norms living in a society. In this context, the Qur’an serves as a norm for Muslims elucidating the implementation of the two. The elucidation is closely related to sunnatullah (natural law). It is here that the Islamic teachings and sunnatullah (natural law) are integrated in Islam.Kata Kunci: Iptek, Alquran, sunnatullah